THE ROLE AND SIGNIFICANCE OF MODERN IT TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN PHARMACEUTICAL SCIENCE - Atakhanov Sanjarbek Anvarovich; Gavharoy Abdulhayeva Husanjon qizi (Bright Mind Publishing, 2025)
This article explains in simple terms why modern IT and Artificial Intelligence (AI) are essential in the pharmaceutical field and what real benefits they provide. First, IT infrastructure helps to digitize laboratory operations, manage production and supply chains, handle data, and ensure cybersecurity — enabling organizations to maintain consistent control, improve quality, and comply with regulatory standards. Next, we present examples of AI applications: drug discovery, analysis of patient data in clinical studies, visual quality control in production, and early detection of adverse effects. On average, AI systems can detect dangerous signals 12 days earlier and reduce false alerts by 32%. Finally, practical recommendations are provided for implementing AI solutions in a sequential, explainable, and safe manner.
Keywords: Pharmaceutical IT; artificial intelligence; clinical trials; pharmacovigilance; real-world evidence; cybersecurity.